Green Discourses in Textbooks: A Critical Eco-Linguistic Analysis of Children’s Literature at Primary Level in Pakistan - Abbas, Waseem; Rasheed, Sabahat; Aleena (Pakistan Journal of Humanities and Social Sciences, 2024)
When it comes to communicating the underlying ideology to the intended audience, textbooks are regarded as an important means of communication. The ideologies that are transmitted through these books are made to be long-lasting through the utilization of a variety of linguistic and semiotic techniques. It is possible for ideologies that are spread through such covert means to leave an indelible mark on the minds of young students for a considerable amount of time. The current research will make use of primary English and Urdu textbooks published by the Punjab Textbook Board (PTB) to conduct an in-depth analysis of green discourses that have been selected for analysis. In the years 2022 and 2023, these books were released to the public. In order to conduct the analysis, linguistic and visual contents that are associated with environmentally friendly discourses will be chosen. When conducting the analysis of the data, the study will make use of a modified research model. For the purpose of conducting an analysis of the chosen data, the Eco-linguistic Discourse Analysis model developed by Stibbe (2015) and the Semiological Discourse Analysis (SDA) model developed by Barthes (1968) will be utilized. An attempt has been made by curriculum designers to raise awareness among young learners about eco-discourses by including environmentally friendly discourses in selected textbooks of PTB at the primary level. This will be revealed by the analysis of the data, which will reveal that this attempt has been made. Furthermore, it will emphasize that primary textbooks are the most effective medium for ideological investment and for molding the mindset of the target audience, which consists of young students who are considered to be the future of a nation, regarding the concept of going green through the incorporation of linguistic and semiotic discourses that are friendly to the environment.